Pengaruh Product, Price, Promotion, dan Place Terhadap Loyalitas Konsumen - Sustiyatik, Enni; Setiono, Beni Agus (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2019)
The purpose of this study was to test and analyze the effect simultaneously and partially Product, Price, Promotion, and Place on customer loyalty. This type of research is an associative study that explains the relationship and influence between Product, Price, Promotion and Place variables on consumer loyalty. The population in this study were consumers who had bought an unknown number of "Flannel" shirts more than 2 times. The sampling process uses a sampling method. The sample used in a population is not yet known, so the sampling technique used is the Lemeshow method, namely 96 respondents. The data analysis technique was carried out using the Multiple Linear Regression method. Based on the research results and data analysis, it was concluded that; (1) Simultaneously the Product, Price, Promotion, and Place variables have a significant effect on consumer loyalty. (2) based on the partial t test the Product, Promotion and Place variables have a significant effect on consumer loyalty. (3) Price variable has no significant effect on consumer loyalty. The most dominant influence is the product variable.